Mathematical methods for hydrodynamic limits - DeMasi, Anna; Presutti, Errico (Lecture Notes in Mathematics, 1991)
Entropy inequalities, correlation functions, couplingsbetween stochastic processes are powerful techniques whichhave been extensively used to give arigorous foundation tothe theory of complex, many component systems and to itsmany applications in a variety of fields as physics,biology, population dynamics, economics,...The purpose of the book is.